Model plant systems in salinity and drought stress proteomics studies: a perspective on Arabidopsis and Sorghum. (26th September 2014) - Ngara, R.; Ndimba, B. K.; Mock, H.‐P.
Abstract More than a decade after the sequencing of its genome, Arabidopsis still stands as the epitome of a model system in plant biology. Arabidopsis proteomics has also taught us great lessons on different aspects of plant growth, development and physiology. Without doubt our understanding of basic principles of plant biology would not have been this advanced if it were not for knowledge gained using Arabidopsis as a model system. However, with the projections of global climate change and rapid population growth, it is high time we evaluate the applicability of this model system in studies aimed at understanding abiotic stress tolerance and adaptation, with a particular emphasis on maintaining yield under hot and dry environmental conditions. Because of the innate nature of sorghum's tolerance to drought and moderate tolerance to salinity stresses, we believe sorghum is the next logical model system in such studies amongst cereals. In this acute view, we highlight the importance of Arabidopsis as a model system, briefly discuss its potential limitations in drought and salt stress studies, and present our views on the potential usefulness of sorghum as a model system for cereals in drought and salinity stress proteomic studies.